Trump s Twitter Propaganda During Covid-19 - Muqsith, Munadhil Abdul; Kuswanti, Ana; Pratomo, Rizky Ridho; Muzykant, Valerii L. (Universitas Semarang, 2021)
During the early Covid-19 pandemic, led by controversial presidential figure Donald Trump, the US seemed to be overwhelmed by this microbial creature, proving to be one of the countries with the most Covid-19. Besides health impacts, there are many multi-effects afterward, such as economic, social, political, and so on, that must be faced after this Covid-19 outbreak. Moreover, the US will hold a presidential election in November 2020. This challenge makes Trump must focus on how to complete Covid-19 while maintaining electability as President. One of the methods adopted is by forming narration through Twitter. Donald Trump is an active Twitter user who often tweets about his stance. Therefore, this study wants to analyze Trump's Twitter tweet content based on propaganda based on six propaganda classifications based on Holly Thayer's Theory. The quantitative content analysis method is the systematic and replicable examination of symbols of communication. The object of research in this article is Twitter's @realDonaldTrump tweet. We analyzed Donald Trump's Twitter content in the period 1 March 2020-27 May 2020 with a systematic random sample method. Our result shows that Trump constructs a message to support his policy and maintain his electability.